Improvement in nutritional quality and thermal stability of palm olein blended with macadamia oil for deep-fat frying application - Koohikamali, Sara (J Food Sci Technol, 2019)
This study aimed to investigate the suitability of refined bleached deodorized palm olein oil (RBD POO) and Macadamia integrifolia oil (MO) blend as deep-fat frying substitute. Oxidative and hydrolytic stability of MO, POO and blends during 15 days of storage under accelerated oxidation condition (65 °C ± 1) studied by assessing free fatty acids (FFA), peroxide (PV), anisidine (AV) and TOTOX (TV) values. Blends formulated with POO: MO at 100:0, 75:25, 50:50, 25:75 and 0:100. Blending significantly affected the fatty acid profile, smoke point, FFA, PV, AV and TV of all samples (p < 0.05). Both independent variables (storage time and type of oil) and their interaction had significant effect on FFA, PV, AV and TV (p < 0.05). On day 15, the highest and the lowest FFA observed for MO and POO, respectively. The significant difference between FFA of MO and POO before incubation and day 15th was due to role of refining process in elimination of initial FFAs from POO. Results of PV, AV and TV showed that the highest and least changes were presented by POO and MO, respectively. Oil blends containing higher proportions of MO with a great percentage of monounsaturated and less polyunsaturated fats were more stable against oxidation. Also, presence of antioxidants played significant role against MO oxidation. From this research, blending POO with MO improved induction period of the blends and inhibited primary and secondary oxidation products formation. Blend 25:75 met the qualitative and nutritional criteria and suggested for formulation of a functional oxidative stable frying medium.